The genus Limbobotys Munroe & Mutuura, 1970 (Lepidoptera, Crambidae, Pyraustinae) from Laos, with the description of a new species and a newly combined species - Ko, Jae-Ho; Bayarsaikhan, Ulziijargal; Kim, Jae Won; Bae, Yang-Seop (Zootaxa, 2025)
The genus Limbobotys is recorded from Laos for the first time, including three newly recorded species (L. ptyophora, L. acanthi, and L. limbolalis), one newly combined species (L. acutangulalis comb. nov.), and one new species (Limbobotys digitatus sp. nov.), described herein. This study provides photographs of adults and genitalia for all examined species, along with an identification key for the Limbobotys species occurring in Laos.